2003
DOI: 10.2320/matertrans.44.1042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additional Elements on the Glass Formation and Corrosion Behavior of Bulk Glassy Cu-Hf-Ti Alloys

Abstract: New bulk glassy (Cu 0:6 Hf 0:25 Ti 0:15 ) 98 M 2 (M = Mo, Ta and Nb) alloys with high thermal stability were synthesized and the effects of additional elements Mo, Ta and Nb on the glass formation and corrosion behavior were examined. The maximum diameter for glass formation of the 2 at%Mo, 2 at%Ta and 2 at%Nb alloys was 1.5 mm, 3.5 mm and 4.0 mm, respectively. The corrosion behavior of the Cu-Hf-Ti-(Mo, Ta and Nb) glassy alloys was examined by weight loss and electrochemical measurements. By substitution of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…However, addition of Ti in both these binary systems greatly increased the glass forming ability (GFA), [5][6][7][8] with the critical diameter for fully amorphous rods being at least 4 mm for Cu 60 Zr 30 Ti 10 , Cu 60 Hf 20 Ti 20 and Cu 55 Hf 25 Ti 20 . On the other hand, it has been shown that small additions of B and Y [7] and of Nb, Ta and Mo [9] reduce the GFA for Cu-Hf-Ti alloys.One of the empirical rules for high GFA in a metallic alloy is that the heat of formation from the constituent elements is negative. Nevertheless, although addition of alloying elements with positive enthalpy of solution should reduce the GFA, there have been some reports that the addition of elements with positive heats of mixing enhances GFA, [10][11][12][13] though Xu et al [10] show that this occurs only when they decrease the melting temperature of the alloy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, addition of Ti in both these binary systems greatly increased the glass forming ability (GFA), [5][6][7][8] with the critical diameter for fully amorphous rods being at least 4 mm for Cu 60 Zr 30 Ti 10 , Cu 60 Hf 20 Ti 20 and Cu 55 Hf 25 Ti 20 . On the other hand, it has been shown that small additions of B and Y [7] and of Nb, Ta and Mo [9] reduce the GFA for Cu-Hf-Ti alloys.One of the empirical rules for high GFA in a metallic alloy is that the heat of formation from the constituent elements is negative. Nevertheless, although addition of alloying elements with positive enthalpy of solution should reduce the GFA, there have been some reports that the addition of elements with positive heats of mixing enhances GFA, [10][11][12][13] though Xu et al [10] show that this occurs only when they decrease the melting temperature of the alloy.…”
mentioning
confidence: 99%
“…However, addition of Ti in both these binary systems greatly increased the glass forming ability (GFA), [5][6][7][8] with the critical diameter for fully amorphous rods being at least 4 mm for Cu 60 Zr 30 Ti 10 , Cu 60 Hf 20 Ti 20 and Cu 55 Hf 25 Ti 20 . On the other hand, it has been shown that small additions of B and Y [7] and of Nb, Ta and Mo [9] reduce the GFA for Cu-Hf-Ti alloys.…”
mentioning
confidence: 99%
“…These materials show excellent properties, for example, high fracture strength, and excellent magnetic properties, strong resistance to corrosion, and so on. [1][2][3][4] Carbon nanotubes (CNTs) are also one of the most advanced materials developed recently. CNTs have high elastic modulus and are one of the most stiffness materials ever made.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson group [1e3] first developed a Cu 47 Zr 11 Ti 34 Ni 8 BMG with a thickness of about 4 mm, opening the door to the fabrication of Cu-based bulk metallic glasses. Subsequently, Inoue group [4e8] prepared a series of new Cu-based BMGs in a CueZreTi ternary system, which has a critical size of 3 mm in diameter, and exhibited very high compressive/tensile yield strengths up to 1.9 GPa.…”
Section: Introductionmentioning
confidence: 99%